2016
DOI: 10.1002/da.22517
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity of Depression and Molecular Markers in a Large Sample of Han Chinese Women

Abstract: Background Major depressive disorder (MDD) has been associated with changes in mean telomere length and mitochondrial DNA (mtDNA) copy number. This study investigates if clinical features of MDD differentially impact these molecular markers. Methods Data from a large, clinically ascertained sample of Han Chinese women with recurrent MDD were used to examine whether symptom presentation, severity, and comorbidity were related to salivary telomere length and/or mtDNA copy number (maximum N=5284 for both molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Bearing in mind we are limited in statistical power by the small sample size of our cohort, and we would not be able to account for effect sizes smaller than beta = 0.29, we found no significant difference in mtDNA copy number or their agerelated dynamic in Holocaust survivors as compared to controls in any generation. This is consistent with findings of no significance difference in telomere length and their agerelated dynamics in Holocaust survivors from the same cohort (Konečná et al, 2019), as mtDNA copy number was previously shown to be negatively correlated with telomere length in chronic stress (Cai et al, 2015b;Edwards et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Bearing in mind we are limited in statistical power by the small sample size of our cohort, and we would not be able to account for effect sizes smaller than beta = 0.29, we found no significant difference in mtDNA copy number or their agerelated dynamic in Holocaust survivors as compared to controls in any generation. This is consistent with findings of no significance difference in telomere length and their agerelated dynamics in Holocaust survivors from the same cohort (Konečná et al, 2019), as mtDNA copy number was previously shown to be negatively correlated with telomere length in chronic stress (Cai et al, 2015b;Edwards et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…As such, alterations to mitochondrial function are increasingly investigated as a key mechanism underlying stress-related conditions (Zhang et al, 2006;Manoli et al, 2007;Su et al, 2008). An increase in mtDNA levels obtained from blood samples has been reported in recurrent Major Depressive Disorder (MDD) (Cai et al, 2015b;Edwards et al, 2016) and a decreased in mtDNA levels has been shown in moderately severe post-traumatic stress disorder (PTSD) (Bersani et al, 2016). Other reports showing conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The China, Oxford and VCU Experimental Research on Genetic Epidemiology (CONVERGE) group recently detected and replicated the first robustly genome-wide statistically significant association between specific molecular variants and MD. 30 In addition, earlier age at worst episode was significantly associated with telomere shortening in this sample 31 . In the context of this success, it is useful to maximize statistical power and to examine AO as a potentially relevant quantitative phenotype.…”
Section: Introductionmentioning
confidence: 72%
“…Recent reports from smaller samples (n~100) suggest associations of depression and psychosocial stress with mitochondrial changes [ 13 , 14 ]. However, few studies [ 15 , 16 ] have addressed associations of mood or depression with mtDNAcn in larger, community-based samples of mid-life and older men and women, and findings regarding the association are inconclusive.…”
Section: Introductionmentioning
confidence: 99%